Tecendo a educação ambiental com fios amazônicos e linhas de dignidade - Silva, Regina Aparecida da (2006)
The village of Guariba is located in the extreme northwest of Mato Grosso. It is a small Amazonian region inhabited by mixed and ethnic groups: rubber tappers, stakeholders, smallholders and villagers – simple people that live in houses with paxiúba palm floors, where their daily lives facing a harsh environment of fighting building their identities and existence. Our contact with the community arose as a result of the Guariba Biodiesel Project which is a part of the federal government’s “Light for all” programme and which is carried out through an agreement between the Federal University of Mato Grosso (UFMT) and the energy company Eletronorte. As subscribers to the phenomenology thought, one of our challenges was to find out the hopes, perceptions and aspirations of the inhabitants of Guariba, so as to enable them to lead more dignified lives. What do the Guariba residents wonder? What are their expectations of a good education? Facing so much environmental conflict, how does this village perceive a healthy environment? What does ‘quality of life’ mean to them? Could it be that apart from conventional indicators - such as the Index of Human Development - IHD, or the Poverty Line – is it possible that the community itself could create its own index? In trying to improve the lot of the inhabitants of Guariba it might be revealed how much we have yet to learn and that quality of life can never be measured by quantitative criteria it self. In this way, we count on the emergence of a collective effort which strengthens our desires to build ‘Sustainable Societies’, where those people who are more selfless and committed stand out because of their mutual respect for one another and through daring to come up with new concepts that may highlight the choices and options of the populace and their cultures.